Review of Sharia Law on the Tradition of Cutting the Weight of Scales in the Sale and Purchase of Grain 'Urf Perspective - Ariyanto, Risandi Budi; Mus'if, Ach.; Fajar, Fajar (Universitas Trunojoyo Madura, 2023)
This research was motivated by a long-standing tradition of buying and selling grain, namely cutting the weight of scales. The cutting carried out is classified into two types: the rice harvesting method using a combine harvester machine and the rice harvesting method using a threshing machine. This study aims to find out how the sharia reviews the tradition of cutting the weight of scales in buying and selling grain. The method used is field research and descriptive analysis with an empirical normative approach. Data collection by observation, interview, and documentation techniques. Data analysis is inductive. Based on the research results, the tradition of cutting the weight of scales can be said to be 'urf. According to the kind, in terms of its object, it includes 'urf 'amali because it is an activity that has become a habit in society, in terms of its scope, it includes 'urf 'am because it has been widely accepted in society, in terms of validity it includes 'urf sahih because this tradition has become a custom, generally accepted, approved by the community, does not conflict with nash and does not contain harm. According to its terms, the 'urf in force is general, has become public, has provisions in the transaction, and does not conflict with nash. According to the criteria of his argument 'urf, cutting the weight of the scales aims to preserve benefit, does not stand alone without reason, and can support the formulation of Islamic law.